The Effect of Kinesio Taping on Carpal Tunnel Syndrome in Informal Sector Workers - Widodo, Agus; Amithya, Farita Adhynda; Ma’nun, Arumi Lu’lul; Noorrahmah, Azkia; Alvanda, Inggil Catur; Ladjiji, Sri Sulistiani T. (Universitas Muhammadiyah Surakarta, 2026)
Introduction: CTS is a musculoskeletal disorder caused by compression of the median nerve, commonly occurring in informal sector workers, particularly those engaged in repetitive wrist movements, which can lead to reduced hand function and work productivity. This study aims to determine the relationship between occupational risk factors and pain with the Boston Carpal Tunnel Questionnaire (BCTQ) score in informal sector workers with CTS after kinesiotaping. Methods: This study used a quasi-experimental design. Respondents were informal sector workers with CTS symptoms who met the inclusion criteria. The BCTQ score was used as a measure of hand function and CTS symptoms. Statistical analysis used Spearman's correlation test and linear regression. Results: Spearman's correlation analysis showed that age had a weak and insignificant negative correlation with BCTQ scores (sig. 0.170; R = -0.234). Repetitive movements showed a moderate and significant negative correlation (sig. 0.020; R = -0.385). Meanwhile, night pain and daytime pain showed a very strong and significant correlation with BCTQ scores (sig. 0.000; R = 0.928). The results of the linear regression test supported these findings, in which age (sig. 0.705) and repetitive movements (sig. 0.894) had no significant effect on BCTQ scores, while night pain and daytime pain showed a significant effect on increasing BCTQ scores. Conclusion: Kinesiotaping is effective in reducing BCTQ scores in patients with carpal tunnel syndrome (CTS), particularly through the reduction of pain, both night pain and activity pain.